Implementasi Benchmarking Tingkatkan Daya Saing dengan Memetakan Keunggulan Industri Lain - Mohamad Afrizal Miradji; Dwi Helena Yuliastari; Ratu Aimartasia; Jea Nur Fitriana (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Inter industry benchmarking has become an important strategy for comanies to improve their competitiveness by mapping the advantages of other sectors. This research addresses the implementation of benchmarking as a transformative tool that allows companies to learn from best practices beyond the traditional boundaries of their industry. With a qualitative descriptive approach, this research explores the latest literature as well as real case studies of Indonesian companies such as PT. Astra International, Bank Mandiri, and Garuda Indonesia. The implementation of benchmarking in the three mentioned companies shows indusa positive impact in the from of increased operational effiensiency, innovation in products or services, and customer satisfaction. This study also highlights the challenges in implementing inter industry benchmarking, including internal resistance, resource limitations, and contextual adaption difficulties. Key success factors such as management commitment, cross-functional collaboration, and the use of modern technology are deteminants of the success of this process. Inter industry benchmarking not only improves efficiency but also creates added value for customers and strengthens the company’s position in the global market.